Radikal böse - Schulte, Christoph,Kant, Immanuel,Nietzsche, Friedrich (Fink, 1988)
Christoph Schulte:
Berlin, Freie Univ., Diss., 1987 u.d.T.: @Schulte, Christoph: Die Karriere des Bösen
Keywords: Hochschulschrift